Tιμιώτερα Books, Talking Objects, Honour and Shame in the Phaedrus - Caserta, Cristiana (Peitho. Examina Antiqua, 2015)
In the Phaedrus, the expression τὰ γεγραμμένα φαῦλα ἀποδεῖξαι, „to demonstrate the inadequacy of its own written” could mean „to make a palinody.” The requirements to define someone as a philosopher that Socrates provides (Phdr. 278) describe in theoretical and normative form what the dialogue has already represented in its dramatic form. Plato has targeted the speech of Lysias and the first speech of Socrates as belonging to a literary genre that is still in statu nascendi: a sophistic conference in which the writing is supposed to be read aloud and there is established a particularl emotional relationship between the reader and listener with the subordination of the latter to the former. For Socrates this relationship should be different and the speeches as well as books should have a completely different intent, content and form: philosopher must offer to the one whom he loves a chaste and virtuous conduct: such conduct, in its imitation of the divine, is precisely what distinguishes him from other scholars: τιμιώτερα. The philosophical relationship must involve a different kind of reading: a silent one that can neutralize the deleterious and seductive effects of the voice. This does not imply, however, that all books are the same. Philosophical writing is not a palindrome on a statue, like a picture. Its qualifying element is the linear and irreversibile sequence. Time flows between one segment and the next. Thus, thoughts presented in writing move in space, whereas characters that have thoughts in them also move over time, changing and modifying themselves. That is precisely how philosophical writing, such as the platonic dialogue, can reproduce logos.